THE INFLUENCE OF SELF-EFFICACY ON COUNSELOR PERFORMANCE AMONG TRAINEE COUNSELOR IN HIGHER EDUCATION INSTITUTION : SUPERVISORY RELATIONSHIP AS MODERATING FACTOR - NUR ASYIQIN, HUSLI (Universiti Malaysia Sarawak (UNIMAS), 2020)
The purposes of this study was to investigate the influence of self-efficacy on counselor performance among trainee counselor in higher education institution and supervisory relationship as the moderating factor. This study implemented a cross-sectional design and use stratified random sampling technique methodology. Data were collected from 90 counselling students that undergo practicum from higher education institution around Malaysia. Few instruments were used to collect data such as demographic form, Counsellor Self-Estimate (COSE), Counsellor Performance Inventory (CPI) and Supervisory Relationship Questionnaire (SRQ) instruments. All of the instruments were translated to Malay language and distributed with dual language. Multiple regression analysis was used to test the moderator effects of supervisory relationship. Supervisory relationship was failed to show moderator effect on counsellor performance. Meanwhile, positive correlation was found between moderator effect on self-efficacy. Result shows that there was significant relationship between self-efficacy and trainee counsellor performance, r(0.00) = p<.05. Hence, self-efficacy had influence on counsellor performance even without supervisory relationship as moderating factor. Consequently, self-efficacy was a vital factor that influence counsellor performance. Therefore, supervisor and trainee counsellor must have a strong supervision relationship with each other. This study expand current knowledge in supervision setting